Захист відомостей про оперативно-розшукову діяльність у площині забезпечення інформаційної безпеки держави - Грібов, М. Л.; Hribov, M. L. (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 1 (108), ч. 1. - С. 264-274, 2025)
Розглянуто юридичні засоби захисту відомостей про оперативно-розшукову діяльність як один з інструментів забезпечення інформаційної безпеки держави. Надано характеристику таких засобів та оцінку їх відповідності сучасним умовам і викликам, а також пропозиції щодо вдосконалення практики їх застосування. Наголошено, що юридичні засоби захисту відомостей про оперативно-розшукову діяльність повинні бути адекватними загрозам, які можуть виникати в разі їх розголошення (лише ті з відомостей, витік яких об’єктивно несе ризики виникнення реальних загроз національній безпеці, потрібно захищати шляхом віднесення до категорії державної таємниці).

The article examines the legal means of protecting information on investigative and detective activities with a view to determining their compliance with the current conditions and challenges. To achieve this goal, the systematic analysis of the Constitution, the Laws of Ukraine “On National Security”, “On Information”, “On Operational and Investigative Activities”, “On Access to Public Information”, “On State Secrets” and a number of by-laws and regulations was applied. The study also analyses the practice of their application. Based on the results of the study, the interrelation and correlation of national security, information security of the State and protection of information on operational and investigative activities are established. From this perspective, the modern legal means of protecting information on operational and investigative activities are characterised and proposals for their improvement are formulated. The results of the work may be used to amend and supplement the Laws of Ukraine “On Operational and Investigative Activities” and “On State Secrets”, as well as the Code of Information Constituting State Secrets and other by-laws. The legal means of protecting information on detective and investigative activities must be commensurate with the threats that may arise in the event of their disclosure. Only the information, the disclosure of which objectively poses a risk of real threats to national security, should be protected by classifying it as a state secret. Such information cannot include general data on the content, forms, methods and organisation of investigative and search activities. They should also not include information about specific operational and investigative measures (complexes of such measures), if the information security of the state cannot be damaged in case of disclosure of such information. It is advisable to protect such information by classifying it as an official secret and (or) establishing (strengthening) liability, including criminal liability, for its disclosure.
Protection of data on operational and investigative activities in terms of ensuring the state’s information security
Keywords: інформаційна безпека; національна безпека; оперативно-розшукова діяльність; оперативні підрозділи; державна таємниця; службова таємниця; кримінальний аналіз; розслідування злочинів; захист інформації; спеціальні знання; information security; national security; investigative and search activities; operational units; state secret; official secret; criminal analysis; investigation of crimes; information protection; special knowledge